إعداد منهج تعليم الغة العربية لأغراض عملية لطلبة الدراسات الأسلأمية في كلية دار الحكمة بكاجنيج, ولأية سلانجور:‏ ‏ دراسة وصفية وتحليلية‏ - Siti Rosilawati bt Ramlan (Kulliyat Ma'arif al-Wahy wa-al-"ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah Maliziya, 2010)
This study aims at preparing the method of teaching Arabic for academic purposes (AAP) to students of Islamic studies at Dar al-Hikmah College. It explains the linguistic needs of the students particularly those specializing in Islamic law and theology. It also describes the position of the Arabic language in Malaysia, putting forth the concept of Arabic for specific purposes, and explaining the position of the Arabic language at Dar al-Hikmah College. A set of questionnaire employing Likert-scale questions is administered to the respondents who are the students of Islamic studies at the college. The researcher finds several significant findings in the curriculum for ASP. The respondents prefer the learning of ASP and its usage in daily life, especially its application in writing research findings. They are also able to participate in Arabic language activities. Out of the various areas of Islamic studies, the respondents demonstrate high preference towards 'ibadah (worship) and 'aqidah (creed). Finally, the researcher discusses several recommendations and lists the references used in the research.